2019
DOI: 10.1128/aem.02487-18
|View full text |Cite
|
Sign up to set email alerts
|

A Combination of Linalool, Vitamin C, and Copper Synergistically Triggers Reactive Oxygen Species and DNA Damage and Inhibits Salmonella enterica subsp. enterica Serovar Typhi and Vibrio fluvialis

Abstract: Inappropriate and disproportionate use of antibiotics is contributing immensely to the development of antibiotic resistance in bacterial species associated with food contamination. The use of natural products in combination can be a potent alternative hurdle strategy to inactivate foodborne pathogens. Here, we explored the pro-oxidant properties of essential oil linalool and vitamin C in combination with copper (LVC) in combating the foodborne pathogens Vibrio fluvialis and Salmonella enterica subsp. enterica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The most probable Vit C antibacterial mechanism of action is based on oxidative stress due to the generation of ROS. According to a very recent study [33], the combination of Vit C with an essential oil and copper resulted in free radical generation through the Fenton reaction. Honey, particularly honeydew honey, is rich in minerals including transition metal ions (Fe and Cu) and polyphenols, and its combination with Vit C may trigger the intracellular production of ROS in bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The most probable Vit C antibacterial mechanism of action is based on oxidative stress due to the generation of ROS. According to a very recent study [33], the combination of Vit C with an essential oil and copper resulted in free radical generation through the Fenton reaction. Honey, particularly honeydew honey, is rich in minerals including transition metal ions (Fe and Cu) and polyphenols, and its combination with Vit C may trigger the intracellular production of ROS in bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a recent study revealed that the antibacterial effect of vitamin C against S. enterica subsp. enterica serovar Typhi and Vibrio fluvialis could be enhanced when applied in a combination with linalool and copper [113]. The effect of this triple combination on bacterial morphology was demonstrated by scanning electron microscopy using V. fluvialis , which showed severe membrane damage, whereas no toxicity could be assessed in human embryonic kidney (HEK293) cells at synergistic concentrations (16.3 μM, 8 mM, and 1.298 mM vitamin C) [113].…”
Section: Anti-salmonella Effects Of Vitamin Cmentioning
confidence: 99%
“…Chickens possess the ability to synthesize VC in kidneys through the glucuronatexylulose-xylulose cycle in the presence of L-gulonolactone oxidase ([EC 1.1.3.8], GLO ). Several researches were reported that VC alone or with other components could decrease SE ( Hernandez-Patlan et al., 2018 ) or other Salmonella species ( Tamoghna Ghosh et al., 2019 ) in vitro. Hernandez-Patlan et al.…”
Section: Introductionmentioning
confidence: 99%